1998
DOI: 10.1070/qe1998v028n03abeh001175
|View full text |Cite
|
Sign up to set email alerts
|

Spatial phase locking of linear arrays of 4 and 12 wide-aperture semiconductor laser diodes in an external cavity

Abstract: We derive the general formula, at a finite cutoff, for the change in the boundary condition of a scalar field in AdS under a Multiple-trace deformation of the dual CFT. Our analysis suggests that fluctuations around the classical solution in AdS should not be constrained by boundary conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Of various types of laser systems, the optical fiber lasers (OFLs) and laser diode arrays (LDAs) have attracted most attention [1][2][3][4][5][6][7][8][9]. And, many useful results have been obtained with these two types of lasers.…”
Section: Introductionmentioning
confidence: 99%
“…Of various types of laser systems, the optical fiber lasers (OFLs) and laser diode arrays (LDAs) have attracted most attention [1][2][3][4][5][6][7][8][9]. And, many useful results have been obtained with these two types of lasers.…”
Section: Introductionmentioning
confidence: 99%
“…Phase locking of laser arrays has attracted considerable interest because it can lead to high output powers while maintaining good output beam quality and stability needed for medical, communications and industrial applications [1], and can serve as a powerful tool to investigate the behavior of coupled nonlinear oscillators and complex network dynamics [2]. Investigations of linear one-dimensional and two-dimensional coupled laser arrays have shown that the connectivity and geometry play an important role in determining the collective properties [3][4][5][6]. Theoretical investigations on the spatiotemporal dynamics and linear stability of coupled lasers on a ring geometry noted the effects of periodic boundary conditions, taking into account either even or odd number of lasers [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…However, with the increases of the emitter stripe width and inter-emitter distance, the emitter fields of an LDA may become incoherent to each other, leading to a poor beam quality. It has been realized that an external cavity can be used to improve the performances of the LDAs [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%